Enhancing E-Commerce To Sustain Economy In Malaysia:Short Review - Abdul Rasib, Amir Hamzah; Mohamad Rafaai, Zubaidi Faiesal; Muhamad Zuki, Mohd Shafinaz (IJSB-International, 2018)
In the past few years,the landscape of Malaysian economy has shifted towards e-commerce in the perspective of production,planning and control.This short review focus on the enhancement of e-commerce to sustain the economy. Among the things that are discussed are the government initiatives on developing e-commerce,how e-commerce is being adapted in Malaysia,and obstacles of setting up businesses online.Apart from that,this paper also reviews the potential of e-commerce,building trust,and ways to improve security and enhance customers’satisfaction. Lastly,matters that are being reviewed in this paper are the challenges and advantages of Malaysia’s e-commerce.